PEMBINAAN KEAGAMAAN DAN EKONOMI BAGI MUALAF OLEH DEWAN DAKWAH ISLAMIYAH INDONESIA DI LAMPUNG - Rini Setiawati; Khomsahrial Romli (Jurnal Dakwah Risalah, 2019)
Converts are people who are new to Islam and do not understand much about Islam. They need guidance regarding Islamic teachings. DDII (Dewan Dakwah Islam Indonesia) Lampung through the Laznas Council of the Da'wah Board of Trustees who are "Guided Residents" also pay attention to the lives of converts around Lampung. The purpose of this study is to describe the implementation of religious and economic guidance for converts by DDII in Lampung. This research is a descriptive qualitative research. The data is analysed interactively. The results of this study are religious guidance activities for converts carried out by firstly instilling the understanding, goals and values of the Islamic religion. These activities conduct regular studies which presenting religious guides to the target villages. Secondly, providing practical religious guidance in reading Iqra and Al-Quran; teaching religious practices and recitation. Thirdly, providing Iqra books, Al-Qur’an or reading books, and prayer tools. While the economic development carried out in three ways namely business training, assistance and investment.